Potensi Wisata Air Terjun Goa Rang Reng Sebagai Objek Wisata Di Desa Bakbakan Gianyar Bali - Mbadhi, Delviana; Yuni, Luh Ketut Herindiyah Kartika; Anggreni, Ni Putu Yunik (Jurnal Daya Tarik Wisata, 2023)
This research was conducted at Goa Rang Reng Waterfall, with the aim of (1) to find out what the tourism potential of Goa Rang Reng Waterfall is, (2) to find out the efforts made by the community to develop the tourism potential of Goa Rang Reng Waterfall. (3) to find out the obstacles faced by managers when managing the object of Goa Rang Reng Waterfall Tourism. This research is a descriptive study. Reng, data collection in the study was carried out by the methods of (1) interviews, (2) observation, (3) documentation, which was then analyzed descriptively qualitatively. The results showed that: (1) the potential possessed by Goa Rang Reng Waterfall was very high. many and very sufficient to support Goa Rang Reng Waterfall in the management as a tourism object in Bakbakan Village, Gianyar Regency. (2) What efforts are being made by the community to manage the tourism potential of Goa Rang Reng Waterfall (3) What are the obstacles faced in managing Goa Rang Reng Waterfall as a tourist attraction in Babakan Village, Gianyar Regency. taken from the research: (1) The natural beauty of Goa Rang Reng Waterfall which is very beautiful with a water discharge that is not too heavy and clear flowing water and the shape of the sloping waterfall makes this waterfall very comfortable and safe for visitors to visit. tourists who want to take a bath or just play with water (2) Goa Rang Reng Waterfall is very easy to find because of its very strategic location which is close to the city center of Ginayar Regency. If tourists from downtown Denpasar to Goa Rang Reng Waterfall only a distance of 29 km or 1 hour drive. In addition, the access road from the village to the location of the Goa Rang Reng Waterfall is very good because the roads are already paved. (3) Goa Rang Reng Waterfall is a new tourist attraction that is developing. Although it is still under development, Goa Rang Reng Waterfall is equipped with several supporting facilities such as parking lots, food and beverage stalls, gazebos, changing rooms, and trash cans.